0577 Sleep Quality and Its Association with Inflammation Over Time in Patients Undergoing Radiation Therapy for Head and Neck Cancer. (25th May 2022) - Ye, Lichuan; Miller, Andrew; Bruner, Deborah; Paul, Sudeshna; Felger, Jennifer; Wommack, Evanthia; Higgins, Kristin; Shin, Dong; Saba, Nabil; Xiao, Canhua
Abstract: Introduction: Sleep disturbance is a prominent concern in patients with cancer with detrimental effect on health outcomes. Although inflammation has been proposed as a potential mechanism of sleep disturbance, there is a dearth of longitudinal data supporting the relationship between cancer-related sleep disturbance and inflammatory markers. The goal of this prospective longitudinal study was to examine the change in sleep quality and its association with inflammatory markers in patients undergoing radiation therapy for head and neck cancer. Methods: A total of 176 patients who had head and neck cancer without distant metastases were assessed before, immediately after, and at 3 and 12 months after radiotherapy. Sleep quality was assessed by the Pittsburgh Sleep Quality Index (PSQI). Peripheral blood inflammatory markers were measured using standard techniques at the same four assessment times. Generalized estimating equations with exchangeable within-subject correlation matrix were used to analyze repeated measures. Results: The participants were mostly middle-aged White (79.5%) men (74.0%) who were married or living with significant others (70.0%) and received concurrent chemoradiotherapy (80.1%). Using the PSQI of 5 as the cut-off, 66.3% of the participants were poor sleepers at baseline, and this rate increased to 82.8% immediately after, then dropped to 56.8% at 3 months and 46.2% 12 months after therapy. Being single (p=0.007), taking antidepressants (p=0.020), and with feeding tube (p=0.01) were identified to be significantly associated with poor sleep quality over time. Controlling for relevant demographic and clinical factors, changes in sleep quality were associated with changes of circulating levels of two inflammatory markers, C-reactive protein (CRP) and interlukin-1 receptor antagonist (IL-1ra). Increased CRP and IL-1ra levels were associated with higher PSQI global scores (beta=0.826, p=0.007 for CRP; beta=1.412, p=0.050 for IL-1ra), indicating worse sleep quality. Conclusion: Patients with head and neck cancer experienced poor sleep quality, especially immediately after treatment completion and in those who were single, depressed, or with feeding tube. Inflammation is associated with cancer-related sleep disturbance and both sleep and inflammation may be potential targets to promote health outcomes in patients with cancer. Support (If Any): The study was supported by NIH/NINR K99/R00NR014587, NIH/NINR R01NR015783, NIH/NCI P30CA138292.